Factors inﬂuencing technology adoption of people with visual impairment: Case study of ﬁnancial transactions through an automatic teller machine (ATM) - Korwatanasakul, Warot (Kasetsart Journal of Social Sciences, 2018)
The objectives of this study were to identify the factors that inﬂuence the technology adoption of ﬁnancial services through a case study of ﬁnancial transactions made via an automatic teller machine (ATM). This study adopted both qualitative and quantitative research methods, including experiments, observation, questionnaires, and focus group in- terviews with 40 observations. The results indicated that the factors inﬂuencing technology adoption include cooperation from all related parties, social acceptance, ease of use, use- fulness in using existing devices such as mobile phones, transaction safety, and security.